NEED ANALYSIS ON THE USE OF ENGLISH IN TRAVEL AGENCIES IN JAKARTA - Nurti Rahayu (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
This research aims to perform need analysis on the use of English in hospitality industries which is emphasized on travel industry in Jakarta. Need Analysis is employed to find out the need of English in specific area, i.e travel agents. This analysis makes sure that the course will contain relevant and useful things to learn. It also enables the course designer to achieve a detailed profile of what the learner needs to be able to do in English in an occupation or study for which he or she is being trained; and to produce a specification of the language skills, functions and forms required to carry out the communication described in the needs profile.The main method of the study was a survey conducted to travel agents in Jakarta.Questionnaires were used to look for primary data. The questionnaires cover different skill areas such as speaking, writing, listening, reading, and vocabulary which are needed in their workplace. Besides, observation and interviews are used to gain the data. These data are used to complete the primary data.The results are then computer-coded and analyzed with the help of the statistical techniques.The results of this research provides a useful input for developing a curriculum or designing an ESP (English for Specific Purposes) to meet the needs of travel agents, and thus ensure the high-quality service for international tourists.